Climatic variables and their relationship with vector-borne disease cases in Colombia, 2011-2021 - Gastelbondo-Pastrana, Bertha; Echeverri-De la Hoz, Daniel; Sanchez, Liliana; García, Yuranis; Espitia-Delgado, Yeiner; Lopez, Yalile; Yasnot-Acosta, Maria F.; Arrieta, German; Mattar, Salim (Frontiers in Tropical Diseases, 2024)
IntroductionVector-borne diseases are a public health problem in tropical countries, especially Malaria, Leishmaniasis, Chagas, and the arboviral diseases Dengue, Chikungunya, and Zika. Tropical diseases represent a significant challenge to health systems in developing countries.ObjectiveThis study aimed to explore the association between climatic variables and primary vector-borne diseases in Colombia between 2011-2021.MethodsA retrospective analysis of the epidemiological data of Malaria, Leishmania, Chagas, Dengue, Chikungunya, and Zika and the climatic data recorded in 2011-2021 was carried out. The cases were obtained from SIVIGILA of the Colombian Ministry of Health. The climatic data were obtained from WorldClim.ResultsLeishmania, Malaria, and Chagas occur in the departments of Caquetá (located in the Amazon rainforest), Chocó (known for its high rainfall), and Casanare (a region with a high prevalence of Chagas disease). There was no statistical correlation between the number of cases and climatic variables, except for malaria cases in which precipitation had a Pearson correlation value of 0.415. The results predicted an increase of 1.469 malaria cases for every unit increase in precipitation. The cases of dengue, Zika, and chikungunya had similar behavior, with the majority occurring in the departments of Valle del Cauca, Antioquia, Norte de Santander, and Bolívar.ConclusionsExcept for Malaria, the distribution of cases did not directly correlate with temperature and precipitation. Temperature and precipitation did not explain the epidemiological profile of the studied diseases.